2013
DOI: 10.4028/www.scientific.net/aef.10.257
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ergonomic Risk of Manual Handling of Patients with MAPO Index and its Relationship with Incidence of Low Back Pain among Nurses

Abstract: Abstract. Low back pain (LBP) is the most common and most costly musculoskeletal disorder among nursing profession. The ergonomic risk factors are common causes of lumbar injury. This study aims to assess the risk of LBP among nurses in different wards of an Iranian subspecialty hospital by means of MAPO method and to investigate if there is any relationship between calculated index and the self-reported LBP. The study was conducted in 16 sections of an Iranian subspecialty hospital including 174 wards. Expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
2
2
Order By: Relevance
“…The study attributes this to the meticulous considerations in room setups, including in-built shower chairs, rails, hoists, wheelchairs, transfer slides, and ample spacing in rooms and bathrooms. While some published studies [30,38,46] establish a significant association between the MAPO index and LBP, this study finds no statistically significant association. Nonetheless, our study validated the effectiveness of the MAPO method in predicting LBP, which was also found in other similar studies [46].…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…The study attributes this to the meticulous considerations in room setups, including in-built shower chairs, rails, hoists, wheelchairs, transfer slides, and ample spacing in rooms and bathrooms. While some published studies [30,38,46] establish a significant association between the MAPO index and LBP, this study finds no statistically significant association. Nonetheless, our study validated the effectiveness of the MAPO method in predicting LBP, which was also found in other similar studies [46].…”
Section: Discussioncontrasting
confidence: 87%
“…Nonetheless, our study validated the effectiveness of the MAPO method in predicting LBP, which was also found in other similar studies [46]. Bivariate regression analysis also fails to establish significant associations between age, length of work, and LBP, contrary to findings in other studies [18,30,[47][48][49][50]. The inconsistencies in these results are attributed to the small sample size and the census method employed in the study.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The minimum MSDs were reported in 27.5%, 28.1%, 14.3%, 24.5%, 5.2%, 13.4%, 11.8%, 16.4%, and 19.1% of the study sample, whereas the highest rate of disorders was reported in 70.73%, 62.1%, 76.1%, 89.1%, 29.5%, 64.5%, 40.5%, 68.7%, and 68.2% for neck, shoulders, upper back, lower back, elbows, hands, hips, knees, and ankles, respectively. [ 1 6 8 9 12 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 ]…”
Section: Methodsmentioning
confidence: 99%